Modern views on the structure and dynamics of biological membranes - Demchenko, A.P. (Вiopolymers and Cell, 2012)
Essential changes have been recently observed in views on the functioning, structural and dynamic properties of biological membranes. The previous results on hierarchical cluster-type structure of membranes and role of protein and lipid components are reconsidered. An established fact of dramatic difference in lipid composition between external and internal monolayers of plasma membranes is important for understanding membrane phenomena. In particular, there exist the differences between monolayers in surface charge and potential, ion binding, interaction with protein molecules, etc. A glycolipid component of outer monolayer and interaction of inner monolayer with cytoskeleton allow the membrane by expanding the asymmetry to attain its important functional properties. All that requires more critical approach to numerous data obtained with simplified biomembrane analogs – lipid and protein-lipid bilayer structures. In the attempts to describe and model the properties of cellular membranes there is a timely necessity to shift from two-dimensionality (which reduces the analysis to membrane plane only) to more realistic three-dimensional models.